Clinical Trials in Metastatic Uveal Melanoma: Immunotherapy - Orloff, Marlana (Ocul Oncol Pathol, 2021)
BACKGROUND: Uveal melanoma (UM) is a rare subtype of melanoma that generally has a poor prognosis once it has metastasized. Clinical trials evaluating immune checkpoint inhibitors (ICIs) in UM have demonstrated response rates lower than those seen in cutaneous melanoma. Despite lower efficacy demonstrated in initial ICI studies, there are a number of ongoing clinical trials investigating novel immunotherapy approaches in UM. SUMMARY: This review aims to summarize important ongoing clinical trials investigating immunotherapeutic approaches in UM and previous trials that have evaluated a number of immunologic interventions. A thorough clinical trial investigation was conducted through clinicaltrials.gov using the disease search terms “uveal melanoma” and “ocular melanoma,” excluding non-immunotherapy-related trials. Here, we report on ICI, vaccine, adoptive T cells, and combination immunotherapy trials in UM. KEY MESSAGES: There is an increasing effort in the search for new, effective therapies for this difficult-to-treat disease, with immunotherapeutic approaches being of particular interest. Increasing knowledge of UM biology and development of new biomarkers will direct future drug development and trial design.